Estimation of the inflammatory burden and its impact after treatment in periodontally affected pre- and postmenopausal women - Jammula Surya Prasanna; Sumadhura Chinta (Wolters Kluwer Medknow Publications, 2022)
Context: Menopause, when menstruation ceases, is seen with an overall increase in body response to inflammation. Gingiva is no such exception. Gingival inflammation which leads to periodontitis is a condition, which is severe inflammatory in nature, affecting the tissues surrounding the teeth. If not treated in time apparently tooth loss might take place. Pre- and postmenopausal conditions, more or less are critical for inflammatory changes. Aims: In this study, among both conditions which one was oppressive and which reciprocated more to scaling was examined. Settings and Design: This study was a cross-sectional interventional study. Materials and Methods: Sixty female subjects aged between 40 and 50 years with periodontitis were recruited. These were meticulously examined by a gynecologist and equated into two groups of 30 patients each, Group I - premenopausal and Group II - postmenopausal women. Plaque index, periodontal index (PDI), and sulcular bleeding index were compared at baseline and 3 months after scaling. Statistical Analysis Used: IBM Statistical Package for the Social Sciences (SPSS) version 21 software was used. An independent sample t-test was applied for percentage decrement and intergroup comparison and paired t-test for intergroup comparisons. Results: Reduction was significant in all the above parameters in both the groups noted on intragroup comparison from baseline to 3 months (P < 0.001). However, the intergroup showed no significance except PDI at baseline. Conclusions: There was a remarkable effect of scaling on inflammatory conditions such as menopause and periodontitis. In the premenopausal stage only, if women undergo periodontal therapy, it can prevent future aggressive inflammatory changes in the postmenopausal stage.